The Art of The Boxtrolls - Brotherton, Philip, (Chronicle Books, 2014)
LAIKA, the studio behind the hit films Coraline and ParaNorman, introduces audiences to a new breed of family: the Boxtrolls, a community of quirky, mischievous creatures who have lovingly raised an orphaned human boy named Eggs in the amazing cavernous home they've built beneath the streets of Cheesebridge. When the town's villain, Archibald Snatcher, comes up with a plot to get rid of the Boxtrolls, Eggs decides to venture above ground where he meets and teams up with fabulously feisty Winnie to devise a daring plan to save Eggs' family. The Art of The Boxtrolls features the amazingly detailed artwork that went into this film's creation, including character sketches, puppets, textiles, set dressing, and 3-D printed facial models, alongside the story of the film's development.